KEBIJAKAN IMIGRASI AUSTRALIA DIBAWAH ERA PERDANA MENTERI JULIA GILLARD TERHADAP PENCARI SUAKA TAHUN 2010-2012 - Muhammad Arkan Multahadi (HI 16 UMY 097, 2016)
*97 Australia is a country which to be one of the asylum seekers’s destination, particularly from countries in the Asian region. Most of them are coming by boat or ship as a transport medium for heading Australia. Because they don’t carry legal documents or the appropriate visa, the Australian government later said the asylum seekers who come by boat such as Irregular Maritime Arrivals or IMAs. IMAs existence is regarded as the embodiment of the government as well as the practice of illegal immigrant smuggling. In 2010, there was an increase in the flow of a high number of IMAs in Australia. In response, the government implemented a policy of punitive asylum seekers by boat. The policies include the implementation of the re-opened Pacific Solution, the return of asylum seekers to the origin country, and Malaysia Solution. This study will look at the factors that influence the government to implement these policies. This study uses the system theory, policy influence system pre theory, and prejudice theory in an attempt to answer the question how the forms of the Australian government implemented policies in dealing with IMAs during the reign of Julia Gillard and the factors that led these policies are finally taken. Methodologically, this study uses descriptive research type, with a range of research is began in 2010 until 2012. The hypothesis is supported by data indicating that the Australian government issued a closed immigration policy to immigrants who came by boat influenced by three factors, the bureaucracy, the party, and the public, with the bases on the consideration of negative prejudice inherent in the boat people as rationalization policy. Key Words : Asylum Seekers, Pasific Solution, Immigration, Bridging Visas, Julia Gillard, Securitization Migration, Policy Influences